Disability outcomes following injury: results from phase one of the prospective outcomes of injury study (POIS). (1st March 2011) - Derrett, S; Langley, J; Hokowhitu, B; Ameratunga, S; Hansen, P; Davie, G; Wyeth, E; Lilley, R
Abstract : Aim: There are gaps understanding outcomes following injury. The Prospective Outcomes of Injury cohort Study (POIS) aims to determine factors (discussed below) influencing the risk of disability up to 2 years after injury. Study Design: Participants from five regions, aged 18–65, were randomly selected from New Zealand's Accident Compensation Corporation (ACC) entitlement claims register. ACC provides no-fault personal injury cover to all residents. Entitlement claims are ones where the injury is severe enough to require 1 week off work or equivalent. The POIS study is at Phase One, with data having been collected about outcomes 3 months after injury.1 Results: 2850 people have been recruited; 24% were hospitalised as a consequence of their injury. Preliminary analysis reveals age, gender, comorbidity, hospitalisation, perceived threat, expectations and pain predicted recovery. Potential predictors to report in September include pre-injury variables (age, gender, comorbidity, satisfaction with social relationships, financial and psychological status) and postinjury variables (health and social services, injury anatomical region and type, pain and expectations of recovery). Outcomes, 3 months after injury, include: health status (EQ-5D and general overall global health rating), participation (in usual activities) and disability (measured by the WHODAS II). Conclusion: Understanding factors that lead to disability will contribute to better targeting of people at risk of poor outcomes and ultimately to service and policy initiatives.1